Integrating Multimodal Arguments Into High School Writing Instruction. (June 2017) - Howell, Emily; Butler, Tracy; Reinking, David
We conducted a formative experiment investigating how an intervention that engaged students in constructing multimodal arguments could be integrated into high school English instruction to improve students' argumentative writing. The intervention entailed three essential components: (a) construction of arguments defined as claims, evidence, and warrants; (b) digital tools that enabled the construction of multimodal arguments; and (c) a process approach to writing. The intervention was implemented for 11 weeks in high school English classrooms. Data included classroom observations; interviews with the teacher, students, and administrators; student reflections; and the products students created. These data, analyzed using grounded-theory coding and constant-comparison analysis, informed iterative modifications of the intervention. A retrospective analysis led to several assertions contributing to an emerging pedagogical theory that may guide efforts to promote high school students' ability to construct arguments using digital tools.